Climate Policies in a Fossil Fuel Producing Country - Demand Versus Supply Side Policies - Taran Fæhn; Cathrine Hagem; Lars Lindholt; Ståle Mæland; Knut Einar Rosendahl (Center for Economic Studies and ifo Institute (CESifo), 2014)
In absence of joint global climate action, several jurisdictions unilaterally restrict their domestic demand for fossil fuels. Another policy option for fossil fuel producing countries, not much explored, is to reduce own supply of fossil fuels. We explore analytically and numerically how domestic demand and supply side policies affect global emissions, contingent on market behaviour. Next, in the case of Norway, we find the cost-effective combination of the two types of policies. Our results indicate that given a care for global emissions, and a desire for domestic action, a majority of emission reductions should come through supply side measures.
Keywords: H23; Q41; Q54; 330; climate policies; carbon leakages; oil extraction; supply side climate policies; demand side climate policies